Cranial variation and taxonomic status of Far-Eastern badgers, with remarks on Pleistocene paleogeography of Meles (Carnivora: Mustelidae) - Andrey Y. Puzachenko; Viktor G. Yudin; Alexei V. Abramov (Vertebrate Zoology)
Abstract Four species of Eurasian badgers (Meles) are widely distributed across Eurasia. Small-sized and dark-coloured Far Eastern M. leucurus amurensis is the most distinctive form among all Asian badgers, M. leucurus. Traditionally, Far Eastern badgers are treated as a subspecies of the M. leucurus. This study aims to revise the geographical variability of the M. leucurus sensu lato from the entire species range (324 adult skulls) and assess the position of the Far Eastern badgers. In addition, 551 adult skulls of the European badger, M. meles, the Southwest Asian badger, M. canescens, and the Japanese badger, M. anakuma, were used for comparison with Asian badgers. Meles leucurus amurensis from the Far East resembles the Japanese M. anakuma in many respects, but is very different from the M. l. leucurus of southern Siberia and Middle Asia. Analysis of palaeontological data suggests that the Far Eastern badgers could have descended from the ancestral “leucurus-like” badger chronospecies known from China since the mid-Early Pleistocene. It then probably dispersed westwards into southern Siberia no later than the MIS9 stage (~ 0.32 Ma), where it evolved into M. leucurus. Previous molecular data suggest that the Japanese badgers are unique, whereas the Far Eastern badgers are closer to Asian badgers from the Urals, Siberia and Tibet. We propose that the Far Eastern badger retains some craniometrics features of the ancestral form of M. leucurus sensu stricto and M. anakuma and should therefore be considered a separate species, M. amurensis Schrenck, 1859 stat. rev. The presumed range of this species is in the Far East, east of the Great Khingan Range to Russian Primorye, Manchuria and the Korean Peninsula and possibly eastern China.